The impact of tourism towards the culture practice of indigenous people / Nor Ana Niza Azhar - Azhar, Nor Ana Niza (2013)
Many sectors of industries contributed to the development of Malaysia, one of the biggest contributors is the tourism sector. Tourism in Malaysia is viewed as a vehicle, which can produce an array of benefits for local community in general, including the minority group of indigenous people. The main purpose of this study is to analyze the impact of tourism in terms of socio-cultural, economic and environmental towards the culture practice of the indigenous people or Orang Asli in the state of Selangor, Malaysia. In order to achieve the purpose of study, questionnaires were distributed to selected respondents in indigenous people’s villages around Selangor, Malaysia. The Department of Orang Asli Development was consulted before collecting the data in order to gather information about the number of population of indigenous people and obtain acquired permission from the authority. The findings revealed that tourism does have impact towards indigenous people community in terms of economic, socio-cultural and environmental. However, despites the impacts of tourism, the indigenous people are still strongly practicing their culture inherited from their ancestors. Since cultural tourism is one of the main contributors to the tourism industry, it is imperative to investigate whether tourism development is coming hand in hand with culture preservation especially to this indigenous people, as previous studies showed that tourists demand for authentic experiences.